Formação Acadêmica em Educação Física: perfis profissionais, objetivos e fluxos curriculares. - Hunger, Dagmar Aparecida Cynthia França [UNESP]; Rossi, Fernanda [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2010)
In this research, characterized as a qualitative study, we aimed to analyze the Job Profiles, Objectives and Curriculum Flows specified in Pedagogical Projects of the undergraduate Courses of Physical Education of public, state and federal universities, in the São Paulo state. We also analyzed their articulations and adequacy to the Institutional Pedagogical Project and Institutional Development Plan. The latest Resolutions of Physical Education in Higher Education and conceptualizations of the Pedagogical Project of Course are presented. The method of approach is current History. There was a documental research in order to analyze the official documents. A limited offering of public courses when compared to private institutions was verified and also, there was a greater offering of bachelor degree courses (expanded and generalized formation) concerning health, sport and leisure fields. Courses defined specifically for teachers' formation and educational gap between the pedagogical discourses and the curriculum structures were also presented. In conclusion, this research indicates the necessity of a change in the curricular mentality in order to implement the pedagogical discourses of courses.

Na presente pesquisa, de natureza qualitativa, objetivou analisar os Perfis Profissionais, Objetivos e Fluxos Curriculares especificados nos Projetos Pedagógicos dos Cursos de Graduação, na área de Educação Física, das Universidades Públicas Estaduais e Federais do Estado de São Paulo, bem como, averiguar suas articulações e adequações ao Projeto Pedagógico Institucional e Plano de Desenvolvimento Institucional. Abordamos as últimas Resoluções da Educação Física no Ensino Superior e conceituações de Projeto Pedagógico de Curso. O método de abordagem é a história do tempo presente. Realizamos pesquisa documental, analisando documentos oficiais. Constatamos limitada oferta de cursos públicos quando comparada as instituições privadas; maior oferta de cursos de bacharelado (formação ampliada e generalizada) nos campos da saúde, do esporte e lazer; cursos definidos especificamente para a formação de professores escolares e descompasso entre os discursos pedagógicos e as estruturas curriculares. Concluímos necessária mudança de mentalidade curricular para se concretizar os discursos pedagógicos dos Cursos.
Professional Formation in Physical Education: job profiles, objectives and curriculum flows
Keywords: Initial Professional Formation; Pedagogical Project of Course; Physical Education